Background to the Science and Policy Report for Tensile Membrane Structures. (2016) - Stranghöner, Natalie; Uhlemann, Jörg; Mollaert, Marijke
Abstract: Nowadays, comprehensive design standards for tensile membrane structures exist neither on European level nor in most European countries on national levels. Currently, the development of a European design standard for membrane structures made from technical textiles and foils is under way. One of the first steps towards a new Eurocode for membrane structures is the preparation of a "Science and Policy Report", so-called "SaP-Report". It is published by the Joint Research Centre (JRC). The SaP-Report for the structural design of membranes was drafted by CEN/TC 250/WG5 "Membrane structures", titled "Prospect for European guidance for the Structural Design of Tensile Membrane Structures". This is an important milestone. The SaP-Report will be the basis of discussions and specifications in the process of creating a new standard throughout the next years. This paper gives background on the meaning, structure and content of the SaP-Report as well as the state of the art regarding the code development.